2018
DOI: 10.1103/physrevb.97.201111
|View full text |Cite
|
Sign up to set email alerts
|

Dislocation charges reveal two-dimensional topological crystalline invariants

Abstract: We identify a one-to-one correspondence between the charge localized around a dislocation characterized by a generic Burgers vector and the Berry phase associated with the electronic Bloch waves of two-dimensional crystalline insulators. Using this correspondence, we reveal a link between dislocation charges and the topological invariants of inversion and rotation symmetry-protected insulating phases both in the absence and in the presence of time-reversal symmetry. Our findings demonstrate that dislocation ch… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 43 publications
1
25
0
Order By: Relevance
“…This one-to-one correspondence only works in crystals possessing an even-fold rotational symmetry, and thus exclude C 3 -symmetric crystals such as the kagome lattice. We wish to remark, however, that even though the breathing kagome lattice does not display a genuine bulk-corner correspondences, its underlying crystalline topology is still reflected in the fractional charge at corners or other topological defects, such as dislocations 50 .…”
Section: Discussionmentioning
confidence: 97%
“…This one-to-one correspondence only works in crystals possessing an even-fold rotational symmetry, and thus exclude C 3 -symmetric crystals such as the kagome lattice. We wish to remark, however, that even though the breathing kagome lattice does not display a genuine bulk-corner correspondences, its underlying crystalline topology is still reflected in the fractional charge at corners or other topological defects, such as dislocations 50 .…”
Section: Discussionmentioning
confidence: 97%
“…In some cases, such topologically nontrivial phases without protected boundary states are characterized by other observable signatures, such as the presence of boundary charges (not states! ), 51,67 or quantized electric 32,33,[68][69][70] or magnetic moments. Such sig-natures of a nontrivial bulk topology are not part of the higher-order bulk boundary correspondence that we establish here, and it is an interesting open problem how they can be incorporated.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the electric polarization of an inversion-symmetric one-dimensional atomic chain is either integer or semi-integer, with a quantized value that does not depend upon microscopic details, but is rather encoded in a gauge-invariant topological index 28 . More recently, it has been shown that excess electronic charges localized at various topological defects, such as dislocations, can be (fractionally) quantized, thus representing yet other incarnations of bulk quantities encoded in topological invariants [29][30][31][32][33][34] . Quantized charges appearing at the corners and disclinations of two-dimensional crystals have been very recently measured in metamaterials [35][36][37] and proposed to appear in recently synthesized materials structures 38 .…”
Section: Introductionmentioning
confidence: 99%
“…This is because Kramers' theorem inevitably doubles the electronic charges, making the real-space invariants partially, often completely, trivial. Progress can be made identifying (partial) Berry phase 29 invariants and/or using Wilson loops as topological indices [45][46][47][48][49] as exemplified by the bulk-dislocation charge correspondence of rotation-symmetric two-dimensional crystals 31 . This additional knowledge, however, does not completely determine the (fractional) quantized electronic charges at the crystal boundaries.…”
Section: Introductionmentioning
confidence: 99%